Real-world clinical course of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) in Japan - Shuntaro Tsutsumi (Orphanet Journal of Rare Diseases, 2019)
Abstract Background As human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a rare chronic neurological disease, large scale studies to collect continuous clinical data have been difficult to conduct. Therefore, the incidence of comorbidities and drug utilization data remain unknown. When conducting trials to develop new drugs in rare disease such as HAM/TSP, historical control data obtained from registry studies would be useful, as cohorts in rare disease tend to be small. Long-term follow-up of patients with a chronic disease can also be challenging. In this study, we addressed the following two goals using registry data on patients (n = 486) enrolled in the Japanese HAM/TSP patient registry “HAM-net” from 2012 to 2016: 1) to clarify the epidemiological information of HAM/TSP such as the incidence of comorbidities and drug utilization and 2) to provide the real-world data on changes in lower limb motor dysfunction. Results In HAM-net-registered patients, common comorbidities were fractures, herpes zoster, and uveitis, with incidences of 55.5, 10.4, and 6.5, respectively, per 1000 person-years. Every year, oral steroid treatment was administered in 48.2–50.7% of the HAM-net-registered patients and interferon-α treatment was used in 2.6–3.5% of patients. The median dose of oral prednisolone was low at 5.0 mg/day. The incidence of fractures and herpes zoster tended to be higher in the steroid-treated group than in the untreated group (fractures: 61.0 vs. 48.3, herpes zoster: 12.7 vs. 8.8, per 1000 person-years). The analysis of chronological change in Osame motor disability score (OMDS) indicated that the mean change in OMDS was + 0.20 [95% confidence intervals (CI): 0.14–0.25] per year in the one-year observation group (n = 346) and + 0.57 (95% CI: 0.42–0.73) over four years in the four-year observation group (n = 148). Significant deterioration of OMDS was noted in all subgroups with varying steroid use status. Conclusions This study revealed the incidence of comorbidities and drug utilization data in patients with HAM/TSP using registry data. Furthermore, this study provided real-world data on chronological changes in lower limb motor dysfunction in patients with HAM/TSP, indicating the utility of these data as historical controls.